Climatological aspects and visitors' comfort perceptions in green open spaces of Samarinda City, East Kalimantan, Indonesia - KARYATI KARYATI; KARMINI KARMINI; DIAH RAKHMAH SARI; YOSEP RUSLIM; MUNA KARHANI (Society for Indonesian Biodiversity, 2025)
Abstract. Karyati, Karmini, Sari DR, Ruslim Y, Karhani M. 2025. Climatological aspects and visitors' comfort perceptions in green open spaces of Samarinda City, East Kalimantan, Indonesia. Biodiversitas 26: 2806-2820. The trees in Green Open Spaces (GOS) play an important role in improving the microclimate, especially in urban areas. This research study aimed to analyze climatological aspects and determine visitor perceptions of GOS comfort in Samarinda City, East Kalimantan, Indonesia. Microclimate elements were measured for 30 days in nine GOS: Anang Hasyim Ecological Park, Cerdas Park, Segiri Park, Samarendah Park, Teluk Lerong Garden Park, Bebaya Park, Muso Salim GOS, RE Martadinata GOS, and Slamet Riyadi GOS. The comfort of these GOS was assessed based on their Temperature Humidity Index (THI) values and the perceptions of visitors to these locations. Visitors' perceptions of microclimate comfort were collected through interviews with 270 respondents (30 respondents in each of the nine GOS). The average light intensity in the nine GOS ranged from 586.3 to 1,117.1 lux, the average air temperature ranged from 28.4-29.1°C, and the average air humidity ranged from 78.1-82.3% during the study period. All of the GOS within this study had a THI of less than 29.0°C and were in the comfortable category, highlighting the positive impact of the microclimate. The analysis of these nine GOS shows that the majority of the 270 respondents have a good perception of their microclimate and comfort. Information about climatological aspects and perceptions of GOS visitors can be used to support databases and recommendations for GOS management related to regional spatial planning.